On Methodological issues in the Indo-European debate By Michel Danino - Marina Silva; John T Koch; Maria Pala; Ceiridwen J Edwards; Pedro Soares; Martin B Richards (Journal of Biosciences, 2019)

Erratum to: Quantifying the legacy of the Chinese Neolithic on the maternal genetic heritage of Taiwan and Island Southeast Asia - Andreia Brandão; Ken Khong Eng; Teresa Rito; Bruno Cavadas; David Bulbeck; Francesca Gandini; Maria Pala; Maru Mormina; Bob Hudson; Joyce White; Tsang-Ming Ko; Mokhtar Saidin; et al. (Human Genetics, 2016)

Quantifying the legacy of the Chinese Neolithic on the maternal genetic heritage of Taiwan and Island Southeast Asia - Andreia Brandão; Ken Khong Eng; Teresa Rito; Bruno Cavadas; David Bulbeck; Francesca Gandini; Maria Pala; Maru Mormina; Bob Hudson; Joyce White; Tsang-Ming Ko; Mokhtar Saidin; et al. (Human Genetics, 2016)
There has been a long-standing debate concerning the extent to which the spread of Neolithic ceramics and Malay-Polynesian languages in Island Southeast Asia (ISEA) were coupled to an agriculturally driven demic dispersal out of Taiwan 4000 years ago (4 ka). We previously addressed this question using founder analysis of mitochondrial DNA (mtDNA) control-region sequences to identify major lineage clusters most likely to have dispersed from Taiwan into ISEA, proposing that the dispersal had a relatively minor impact on the extant genetic structure of ISEA, and that the role of agriculture in the expansion of the Austronesian languages was therefore likely to have been correspondingly minor. Here we test these conclusions by sequencing whole mtDNAs from across Taiwan and ISEA, using their higher chronological precision to resolve the overall proportion that participated in the “out-of-Taiwan” mid-Holocene dispersal as opposed to earlier, postglacial expansions in the Early Holocene. We show that, in total, about 20 % of mtDNA lineages in the modern ISEA pool result from the “out-of-Taiwan” dispersal, with most of the remainder signifying earlier processes, mainly due to sea-level rises after the Last Glacial Maximum. Notably, we show that every one of these founder clusters previously entered Taiwan from China, 6–7 ka, where rice-farming originated, and remained distinct from the indigenous Taiwanese population until after the subsequent dispersal into ISEA.

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Mosaic maternal ancestry in the Great Lakes region of East Africa - Verónica Gomes; Maria Pala; Antonio Salas; Vanesa Álvarez-Iglesias; António Amorim; Alberto Gómez-Carballa; Ángel Carracedo; Douglas J. Clarke; Catherine Hill; Maru Mormina; Marie-Anne Shaw; David W. Dunne; et al. (Human Genetics, 2015)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Karyology and karyotype analysis of diploid freshwater planarian populations of the Dugesia gonocephala group (Platyhelminthes, Tricladida) found in Sardinia - Maria Pala; Salvatore Casu; Giacinta Stocchino (Hydrobiologia, 1999)